Spatial working memory performance in a real museum environment versus computer simulation: A comparison between healthy elderly and young adults. - Korman, Maria; Kizony, Rachel; Hochhauser, Michal; Kuflik, Tsvi; Wecker, Alan J.; Weiss, Patrice L. (Journal of Pain Management, 2016)
In recognition of the limited ecological validity of testing in a laboratory setting, we compared spatial memory performance of healthy young and older adults in a real museum setting and on a computer simulation. In the museum, participants physically moved between display stations to locate hidden tokens; an ongoing representation of previous searches had to be remembered. A comparable task was implemented via mouse actions on a computer simulation. Nine older (60-80 years) and 20 young (20-45 years) adults performed both tasks. The young group was superior to the older group in terms of success and time, and all participants were more efficient within the simulated task. The feasibility of using realistic tasks in a physical location to study spatial memory is discussed.